(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2023)
Nowadays Extensible Mark-up Language (XML) is a dominant technology for formatting and exchanging data across the Internet world. Updating and retrieving a massive amount of XML data is an interesting and active research area. In addition, indexing XML data is a significant task to improve the efficiency of XML queries. Labelling nodes is the used technique for indexing XML data efficiently. There are many labelling schemes that have been proposed. However, these schemes have many limitations and shortcomings. Therefore, this paper aims to propose a new XML labelling scheme that addresses the issue of efficiency of XML query performance. Thus, this paper developed a new XML labelling scheme. Consequently, four experiments were designed in order to evaluate this. The results of these experiments suggest that the proposed scheme achieved the target results and showed an improvement in the performance and the efficiency of labelling XML documents.